Enrichment of heavy metal and risk assessment in surface water of Tunggak River, Gebeng, Pahang. - Nurhidayah, Mohd Zainal (2015)
Surface water includes all water on surface of the earth that can be found in rivers, streams, canals, lakes, wetlands, coastal, ditches, marshes and ponds waters and also appears as in ice and snow. Industrial activities are the main cause for surface water pollution. Therefore, the objectives of this research were to evaluate the enrichment factor of heavy metal from the surface water and to provide the latest level of water pollution in Tunggak River. To fulfil it, several water quality parameters were analyzed, with collection of data from 3 different stations during February-March 2015 across the river basin. The in-situ parameters were temperature, pH, turbidity, Electric Conductivity and Dissolved Oxygen. Meanwhile, for ex-situ parameters such as Biochemical Oxygen Demand, Chemical Oxygen Demand, Total Suspended Solids, Ammoniacal Nitrogen and selected heavy metal, analysis were conducted by using DR/2500 Spectrophotometer and Atomic Absorption Spectrometer using APHA and HACH standard methods. Later, the results from all the tests were used to calculate the Enrichment Factor, National Water Quality Standard and Water Quality Index to indicate the quality of the study area. The study revealed that some trace metals were found in surface water of the Tunggak River, Gebeng, most probably caused by the industrial activities and the availability of numerous of factories surrounded the river. From the results, the authorities should implement the suitable watershed protection and management system to control the pollution of the surface water.